Sulfasalazine Induced Toxic Epidermal Necrolysis in a Rheumatoid Arthritis Patient-A Case Report - Raveendran, Adhirai; Betkerur, Jayadev; Archana, Sindhughata Ashok; Kumar, Adusumilli Pramod; Ramesh, Madhan; Parthasarathi, Gurumurthy (Indian Journal of Pharmacy Practice)
Toxic epidermal necrolysis also known as Lyell's syndrome is a rare but potentially life threatening severe cutaneous adverse reaction with widespread epidermal detachment and mucosal erosions. Drug exposure and a resulting hypersensitivity reaction is the cause of the very large majority of cases of Steven Johnson Syndrome. This is a case of 34-year-old female patient, presented to hospital with a presentation of rash, throat pain, fever and eye pain with redness. The patient medical history shows that she is a known case of rheumatoid arthritis and treated with sulfasalazine 500 mg, paracetamol 650 mg and aceclofenac 100 mg which she took for 16 days and injection methylprednisolone IM for 20 days. She has no improvement of joint pain and developed few fluid filled lesions in oral cavity, which ruptured spontaneously. She gives history of a pain and burning sensation while swallowing and her first biopsy report showed erythema multiforme on hospital admission and was finally diagnosed as Toxic Epidermal Necrolysis. Patient was treated with capsule cyclosporine and injection dexamethasone. The patient showed good response to treatment and lesions, erosions decreased within span of 20 days. Toxic epidermal necrolysis is a severe cutaneous adverse drug reactions associated with high mortality. Patients prescribed with sulfanamides like sulfasalazine, educating them regarding the appropriate use of medications are of utmost importance.
Keywords: Toxic Epidermal Necrolysis; Severe Cutaneous Adverse Drug Reaction; Sulfasalazine